Child soldiers and transitional justice: protecting the rights of children involved in armed conflicts - Nylund, Bo Viktor (Series on transitional justice, 2016)
This book adapts existing theoretical frameworks of transitional justice in order to analyse child recruitment, with a view to demonstrating how a society can address the issue in a holistic way. It systematises relevant knowledge across a range of legal fields to allow for greater understanding of the law and principles, and a more informed basis for practical engagement with transitional justice mechanisms